EVALUASI DAN PENGEMBANGAN PENGELOLAAN OBAT: GAMBARAN DI RUMAH SAKIT GIGI DAN MULUT PENDIDIKAN FAKULTAS KEDOKTERAN GIGI UNIVERSITAS TRISAKTI - Sarwono, Aditya Pratama (LPPM Universitas Pekalongan, 2019)
Medication management in hospitals is a crucial aspect of providing safe and high-quality healthcare services. At the Dental and Oral Hospital of the Faculty of Dentistry, Trisakti University (RSGM-P FKG Usakti), the challenge of medication management becomes more complex due to the need to integrate clinical and academic requirements. This study aims to evaluate and improve medication management at RSGM-P FKG Usakti to meet the highest standards in healthcare and education. The research methods include literature review, policy analysis, data collection and analysis, interviews, and direct observation. The results show that RSGM-P FKG Usakti has implemented comprehensive medication management standards, but there are still areas that need further development, such as enhancing inter-departmental coordination, adjusting medication planning with the latest medical developments, and strengthening antimicrobial resistance control programs. In conclusion, continuous development is necessary to improve the efficiency, effectiveness, and quality of medication management at RSGM-P FKG Usakti.